Simple dynamic energy efficient field oriented control in induction motors - Diachenko, Grygorii; Schullerus, Gernot (My University, 2015)
The current paper discusses the optimal choice of a filter time constant for filtering the steady state flux reference in an energy efficient control strategy for changing load torques. It is shown that by appropriately choosing the filter time constant as a fraction of the rotor time constant the instantaneous power losses after a load torque step can be significantly reduced compared to the standard case. The analysis for the appropriate choice of the filter time constant is based on a numerical study for three different induction motors with different rated powers.
Keywords: energy efficiency; енергоефективність; field-oriented control; power losses; втрати потужності; filtering; фільтрація; dynamic operation